2011
DOI: 10.1161/circep.110.961508
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Effects of Epicardial Radiofrequency Applications Delivered on Epicardial Coronary Arteries

Abstract: Background-Epicardial coronary injury is by far the most feared complication of epicardial ablation. Little information is available regarding the chronic effects of delivering radiofrequency in the vicinity of large coronary vessels, and the long-term impact of this approach for mapping and ablation on epicardial vessel integrity is poorly understood. Therefore, the aim of this study was to characterize the acute and chronic histopathologic changes produced by in vivo epicardial pulses of radiofrequency ablat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…In a porcine model, RF ablation proximal to the coronary arteries led to chronic histopathologic changes, characterized by tunica intima and media thickening with replacement of the smooth muscle cells with extracellular matrix; however, no significant stenosis was observed up to 70 days after ablation. 5 In the present study, significant LMCA and LAD stenoses developed 4 months after RF ablation. Intravascular ultrasound showed positive remodeling characteristics in the LAD lesion.…”
supporting
confidence: 51%
“…In a porcine model, RF ablation proximal to the coronary arteries led to chronic histopathologic changes, characterized by tunica intima and media thickening with replacement of the smooth muscle cells with extracellular matrix; however, no significant stenosis was observed up to 70 days after ablation. 5 In the present study, significant LMCA and LAD stenoses developed 4 months after RF ablation. Intravascular ultrasound showed positive remodeling characteristics in the LAD lesion.…”
supporting
confidence: 51%
“…17 Several studies have demonstrated that acute vascular wall changes, including endothelial disruption, neointimal thickening, and intravascular thrombosis, occur when delivering RFA in the vicinity of a coronary artery with risk of chronic vascular damage inversely proportional to vessel size. 19,20 Moreover, more significant changes were noted to only occur in vessels of small calibre with the suggestion that larger vessels are protected from such changes due to greater blood flow. 13 RF application over or immediately adjacent to a coronary artery is best avoided, and based on our data, coronary injury is greater when CF is high.…”
Section: Neurovascular Injury and Epicardial Ablationmentioning
confidence: 94%
“…Viles-Gonzalez and co-workers delivered RF lesions within 1 mm of the coronary arteries in seven pigs, and examined the acute (20 days) and chronic (70 days) effects. 103 In both the acute and chronic specimens, intimal and medial thickening was seen, with replacement of smooth muscle cells by extracellular matrix. No significant stenosis was observed up to 7 days after ablation.…”
Section: Collateral Injury and Complications (Fig 10)mentioning
confidence: 96%